Refund of State Financial Losses in Realizing the Welfare State of Law - Mustawa, Mustawa; Hamid, Abd. Haris; Purwanda, Sunardi (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2022)
The concept of punishment is not only emphasized to the subject of the perpetrator, but also the consequences that can be caused need to be accounted. What is the ideal form of punishment for perpetrators of corruption. Does it really need extraordinary efforts to deal with this crime? This article was a type of normative research. The approach used in normative research was the statutory approach, which is an approach taken by examining all laws and regulations related to the legal issues being handled. Refund of state financial losses, especially corruption in Indonesia, is not easy and can be done. The perpetrators of corruption have very strong access to a wide network of power that is difficult for law enforcement to reach. This article describes the regulation of the return of state financial losses due to criminal acts that can be carried out through two legal instruments, namely criminal law instruments and civil law instruments.